The Light vs. Dark Triad of Personality: Contrasting Two Very Different Profiles of Human Nature - Kaufman, Scott Barry; Yaden, David Bryce; Hyde, Elizabeth; Tsukayama, Eli (Frontiers in Psychology, 2019)
While there is a growing literature on “dark traits” (i.e., socially aversive traits), there has been a lack of integration with the burgeoning research literature on positive traits and fulfilling and growth-oriented outcomes in life. To help move the field toward greater integration, we contrasted the nomological network of the Dark Triad (a well-studied cluster of socially aversive traits) with the nomological network of the Light Triad, measured by the 12-item Light Triad Scale (LTS). The LTS is a first draft measure of a loving and beneficent orientation toward others (“everyday saints”) that consists of three facets: Kantianism (treating people as ends unto themselves), Humanism (valuing the dignity and worth of each individual), and Faith in Humanity (believing in the fundamental goodness of humans). Across four demographically diverse samples (N=1,518), the LTS demonstrated excellent reliability and validity, predicting life satisfaction and a wide range of growth-oriented and self-transcendent outcomes above and beyond existing measures of personality. In contrast, the Dark Triad was negatively associated with life satisfaction and growth-oriented outcomes, and showed stronger linkages to selfish, exploitative, aggressive, and socially aversive outcomes. This exploratory study of the contrasting nomological networks of the Light vs. Dark Triad provides several ways forward for more principled and data driven approaches to explore both the malevolent and beneficent sides of human nature.